2019
DOI: 10.1515/chem-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Valency-based molecular descriptors of Bakelite network BNmn$B\text N_{m}^{n}$

Abstract: Bakelite network $BN_{m}^{n}$is a molecular graph of bakelite, a pioneering and revolutionary synthetic polymer (Thermosetting Plastic) and regarded as the material of a thousand uses. In this paper, we aim to compute various degree-based topological indices of a molecular graph of bakelite network $BN_{m}^{n}$. These molecular descriptors play a fundamental role in QSPR/QSAR studies in describing the chemical and physical properties of Bakelite network $BN_{m}^{n}$. We computed atom-bond connectivity ABC its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recent works carried out by Cowperthwaite & Reynolds (2014), Hogg & Reynolds (2016) and Ahmad et al (2018) have shown that for standard optically thick and geometrically thin disks the propagation time-scales are frequency dependent and are different from the viscous ones. Maqbool et al (2019) quantified this behavior for hot, optically thin, geometrically thick flows considering the propagation time from the transition region onwards.…”
Section: Stochastic Propagation Modelmentioning
confidence: 99%
“…Recent works carried out by Cowperthwaite & Reynolds (2014), Hogg & Reynolds (2016) and Ahmad et al (2018) have shown that for standard optically thick and geometrically thin disks the propagation time-scales are frequency dependent and are different from the viscous ones. Maqbool et al (2019) quantified this behavior for hot, optically thin, geometrically thick flows considering the propagation time from the transition region onwards.…”
Section: Stochastic Propagation Modelmentioning
confidence: 99%
“…According to Cowperthwaite & Reynolds (2014), the time-lag expected in stochastic propagation is frequency dependent. Ahmad et al (2018) have shown that for standard stable gas pressure dominated disk the propagation timescale is frequency dependent for frequencies higher than the local viscous time-scale. While these results are indicative, one should bear in mind that they are for standard optically thick disks, and it is not certain how quantitatively different would the results be for a hot optically thin, geometrically thick flow and when the propagation time being considered is from the transition region on wards.…”
Section: Comparison With Other Propagation Modelsmentioning
confidence: 99%
“…However, one interesting feature of these simulations is that the propagation time-scales can be frequency dependent and are not necessarily the same as the viscous ones. Using simple time dependent standard disk equations, Ahmad et al (2018) also showed that this is the case and quantify the frequency dependent behaviours. However, these results are for standard outer disks extending to the last stable orbit and it is not clear how the results would change if the standard outer disk is truncated at some distance from the black hole and has a hot inner flow (Yuan & Narayan 2014).…”
Section: Introductionmentioning
confidence: 97%
“…In an earlier paper [60], we discussed and computed several results regarding bakelite network, see figure (6), that are presented here to use them for comparative analysis.…”
Section: Bakelite Networkmentioning
confidence: 99%